Antithrombotic and Anticoagulant Activity of Depolymerized Fragment of the Glycosaminoglycan Extracted from Stichopus japonicus Selenka - Suzuki, Norihiko; Kitazato, Kenji; Takamatsu, Junki; Saito, Hidehiko (Thrombosis and Haemostasis, 1991)
The antithrombotic and anticoagulant activities of depolymerized fragment (DHG-l) of glycosaminoglycan extracted from Stichopw japonicus Selenka (FGAG) were compared with those of unfractionated heparin (UFH) or low molecular weight heparin (LMWH). DHG-1 at more than 0.3 mg/kg i. v. significantly prevented death of mice treated with thrombin (800 U/kg i.u.). Under the same conditions, FGAG, UFH and LMWH significantly prevented death of mice at more than 0.3, 0.3 and 0.6 mg/kg i.v., respectively. In normal plasma, the concentration required to double the activated partial thromboplastin time (doubling APTT) of DHG-I, FGAG, LMWH and UFH were 12.0, 2.4, 5.8, and 1.2 μg/ml, respectively. In antithrombin III (AT Ill)-depleted plasma, doubling APTT of DHG-1, FGAG, and UFH were 11.3, 2.1, and 18.5 μg/ml, respectively. Prothrombin activation in contact-activated plasma was inhibited completely for 60 s at doubling APTT by all glycosaminoglycans used in this study. DHG-I, however, showed much less antithrombin activity than UFH as tested by thrombin clotting time in plasma and chromogenic assay in the presence of AT III. Moreover, DHG-1 showed much less inhibitory activity on factor Xa, factor IXa, and glass surface-induced factor IXa generation than UFHThese results suggested that DHG-1 is one of the promising antithrombotic agents with quite different anticoagulant property from UFH or LMWH.